Formation of Twisted β‐Sheet Tapes from a Self‐Complementary Peptide Based on Novel Pillararene‐GCP Host–Guest Interaction with Gene Transfection Properties. Issue 39 (12th June 2018) - Hu, Xiao‐Yu; Ehlers, Martin; Wang, Tingting; Zellermann, Elio; Mosel, Stefanie; Jiang, Hao; Ostwaldt, Jan‐Erik; Knauer, Shirley K.; Wang, Leyong; Schmuck, Carsten
Abstract: Small peptides capable of assembling into well‐defined nanostructures have attracted extensive attention due to their interesting applications as biomaterials. This work reports the first example of a pillararene functionalized with a guanidiniocarbonyl pyrrole (GCP)‐conjugated short peptide segment. The obtained amphiphilic peptide 1 spontaneously self‐assembles into a supramolecular β‐sheet in aqueous solution based on host–guest interaction between pillararene and GCP unit as well as hydrogen‐bonding between the peptide strands. Interestingly, peptide 1 at low concentration shows transitions from small particles to "pearl necklace" assemblies, and finally to branched fibers in a time‐dependent process. At higher concentration, it directly assembles into twisted β‐sheet tapes. Notably, without pillararene moiety, the control peptide A forms α‐helix structure with morphology changing from particles to bamboo‐like assemblies depending on concentration, indicating a significant role of the pillararene‐GCP host‐guest interaction for the secondary structure formation. Moreover, peptide 1 can serve as an efficient gene transfection vector. Abstract : A novel pillararene functionalized with a GCP‐conjugated short peptide segment can self‐assemble into a supramolecular β‐sheet in aqueous solution based on host–guest interaction between pillararene and GCP unit as well as hydrogen‐bonding between the peptide strands. Notably, without a pillararene moiety, the GCP‐conjugated control peptide A forms a supramolecular α‐helix. Moreover, the amphiphilic peptide studied can achieve intracellular DNA delivery and gene transfection.